IMPLEMENTASI PENDEKATAN DIFERENSIASI DALAM MENGATASI DISPARITAS PEMAHAMAN SISWA PADA MATERI PERKALIAN DI MATEMATIKA KELAS III SEKOLAH DASAR - Alfina Febrianti; Panjaitan, Mei Seven; Khatimah, Husnul; Risdalina, Risdalina; Destrinelli, Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the differentiated approach in addressing disparities in students’ understanding of multiplication material in Grade III at SDN 34/I Teratai. The research employed a Classroom Action Research (CAR) method using the spiral model of Kemmis and McTaggart, consisting of two cycles, with a total of 23 student participants. Data were collected through observation, documentation, and learning outcome tests. The results showed that the differentiated approach significantly improved students’ understanding, as indicated by an increase in the average score from 68.20 in the first cycle to 82.60 in the second cycle, and an increase in classical learning completeness from 56% to 80%. This approach effectively accommodated differences in students’ learning styles, interests, and readiness, thus positively impacting learning outcomes. Therefore, implementing a differentiated approach is a viable alternative strategy to create inclusive and effective learning environments.